2018
DOI: 10.1002/ana.25375
|View full text |Cite
|
Sign up to set email alerts
|

Brain state–dependent stimulation boosts functional recovery following stroke

Abstract: Objective: Adjuvant protocols devised to enhance motor recovery in subacute stroke patients have failed to show benefits with respect to classic therapeutic interventions. Here we evaluate the efficacy of a novel brain-state dependent intervention based on known mechanisms of memory and learning, that is integrated as part of the weekly rehabilitation program in subacute stroke patients. Methods: Twenty-four hospitalized subacute stroke patients were randomly assigned to two intervention groups; 1. The associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(98 citation statements)
references
References 39 publications
1
95
1
Order By: Relevance
“…Moreover, we evaluated other metrics (MEPs for the corticospinal excitability for healthy individuals; clinical scales, range of motion and velocity for the patient; and satisfaction with the process of intervention for all participants) to support our novel approach to a clinical therapy. Regarding TMS, although there are limitations and results are not consistent when extrapolating corticospinal excitability improvement to learning processes in rehabilitation (Carson et al, 2016), several recent studies point out that an increase in corticospinal excitability may be related to an improvement in motor learning (Kida et al, 2016;Naros et al, 2016;Mawase et al, 2017;Christiansen et al, 2018;Raffin and Siebner, 2018;Mrachacz-Kersting et al, 2019), and moreover, there is a relationship between the improvement in the metrics in the robotic therapy, motor learning, and corticospinal excitability enhancement in healthy subjects (Perez et al, 2004). For this reason, we decided to use TMS as a valid technique to assess the corticospinal excitability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we evaluated other metrics (MEPs for the corticospinal excitability for healthy individuals; clinical scales, range of motion and velocity for the patient; and satisfaction with the process of intervention for all participants) to support our novel approach to a clinical therapy. Regarding TMS, although there are limitations and results are not consistent when extrapolating corticospinal excitability improvement to learning processes in rehabilitation (Carson et al, 2016), several recent studies point out that an increase in corticospinal excitability may be related to an improvement in motor learning (Kida et al, 2016;Naros et al, 2016;Mawase et al, 2017;Christiansen et al, 2018;Raffin and Siebner, 2018;Mrachacz-Kersting et al, 2019), and moreover, there is a relationship between the improvement in the metrics in the robotic therapy, motor learning, and corticospinal excitability enhancement in healthy subjects (Perez et al, 2004). For this reason, we decided to use TMS as a valid technique to assess the corticospinal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the use of the proposed ankle rehabilitation robot would promote motor learning and increase corticospinal excitability of the dorsi-plantarflexor muscles. Although there is not a clear relationship between motor learning and corticospinal excitability (Bestmann and Krakauer, 2015), several authors have established a relation between them (Perez et al, 2004;Kida et al, 2016;Naros et al, 2016;Mawase et al, 2017;Christiansen et al, 2018;Raffin and Siebner, 2018;Mrachacz-Kersting et al, 2019). Corticospinal excitability can be assessed with Transcranial Magnetic Stimulation (TMS), by eliciting Motor Evoked Potentials (MEPs) (Rotenberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, with PAS protocols that induces spike-timing-dependent plasticity ( 76 78 ), synaptic transmission can be potentiated or depressed depending on the relative timing between the presynaptic and postsynaptic spiking ( 77 , 85 , 86 ), and repeated application of TMS-PNS PAS can potentiate corticospinal-motoneuronal transmission and excitability in people with MS ( 43 , 45 ). A similar PAS concept can also be applied to cortical neurons ( 79 , 87 , 88 ). Therapeutic potency of PAS in people with MS is yet to be determined.…”
Section: Neuromodulation For Rehabilitation In People With Msmentioning
confidence: 99%
“…An example of a context which requires reliable labelling of ERPs is in the delivery of an endogenous paired associative stimulation (ePAS) intervention, a non-invasive neuromodulatory intervention that has been shown to modulate corticomotor excitability in healthy people [7,[17][18][19] and people with stroke [20,21]. Based on traditional paired associative stimulation (PAS) [22][23][24], ePAS involves the delivery of 50 single pulses of peripheral electrical stimulation, each paired with an endogenous ERP signal known as the movement related cortical potential (MRCP) [7,17,18,20,21]. The MRCP is observed as an individual prepares and executes a voluntary or imagined movement [25,26] and is characterized by a slow (≈0.5 Hz) negative potential which begins approximately 1.5 to 2 s prior to movement and peaks around the onset of movement (amplitude -5 to -30 uV) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…This timing is achieved by triggering the peripheral electrical stimulation at a set number of milliseconds before the PN of the MRCP to account for the conduction time between the peripheral nerve and the M1 [7]. However, the neuromodulatory effects of ePAS present considerable between-participant variability [17][18][19][20][21]. For example, Olsen et al [17] showed increases in corticomotor excitability ranging from 4%-396% (n = 10).…”
Section: Introductionmentioning
confidence: 99%